2014
DOI: 10.1111/jdv.12648
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a smartphone application using fractal image analysis of pigmented moles compared to clinical diagnosis and histological result

Abstract: The smartphone application using fractal analysis might be a promising tool in the pre-evaluation of pigmented moles by laypersons, while it is to date inferior to the diagnostic evaluation by a dermatologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 9 publications
3
100
0
2
Order By: Relevance
“…The sensitivity of teledermatology diagnosis ranged from 73% to 97%, and the specificity ranged from 73% to 83%. 28,30,32,33 Results comparing FTF and histopathological diagnosis were slightly better than the teledermatology diagnoses by Maier et al 28 and Tan et al, 32 but no statistical difference was found by the former and there was no direct comparison of results between telediagnosis and FTF diagnosis by the latter.…”
Section: Diagnostic Accuracymentioning
confidence: 41%
See 3 more Smart Citations
“…The sensitivity of teledermatology diagnosis ranged from 73% to 97%, and the specificity ranged from 73% to 83%. 28,30,32,33 Results comparing FTF and histopathological diagnosis were slightly better than the teledermatology diagnoses by Maier et al 28 and Tan et al, 32 but no statistical difference was found by the former and there was no direct comparison of results between telediagnosis and FTF diagnosis by the latter.…”
Section: Diagnostic Accuracymentioning
confidence: 41%
“…[27][28][29][30][31][32][33][34][35] Studies were predominantly from high income countries. Three studies were from the United States, 30,34,35 two studies from Germany, 27,28 and one from each of the following countries: Australia, 29 South Korea, 31 and New Zealand. 32 There was one study performed in Brazil, 33 which is an upper middle income country (Table S4).…”
Section: Diagnostic Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one studies were included in the review ( Figure 1): twenty studies had been published as original articles [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], six were conference papers [51][52][53][54][55][56] and five were research letters [57][58][59][60][61].…”
Section: Resultsmentioning
confidence: 99%